Boundedness of the fractional maximal operator on variable exponent Lebesgue spaces: a short proof - Gorosito, Osvaldo Prudencio (2012)
We give a simple proof of the boundedness of the fractional maximal operator providing in this way an alternative approach to the one given by C. Capone, D. Cruz Uribe and A. Fiorenza in citeCCUF.